A simple bicriteria heuristic approach for an elective surgery scheduling problem - Marques, I.; M.E. Captivo; Pato, M.V. (EURO XXVI 2013, 2013)
The healthcare sector in Portugal requires an efficient use of resources and the simultaneous reduction of waiting lists. This becomes of even higher relevance to the operating theatre unit of a hospital. A bicriteria surgery scheduling problem arising in a Lisbon hospital is presented. Two conflicting objectives are considered: maximize surgical suite occupation and maximize the number of surgeries scheduled. A constructive and improving heuristic specially designed to address both objectives of the problem was developed. Results obtained with real data from the hospital are presented.